2007
DOI: 10.1063/1.2721365
|View full text |Cite
|
Sign up to set email alerts
|

Reduced surface electron accumulation at InN films by ozone induced oxidation

Abstract: A room temperature ozone induced oxidation of thin InN films is proposed to improve the electric transport properties. The sheet carrier density is reduced upon oxidation by a value which is in the order of the electron concentration of an untreated InN surface. Thus, ozone effectively passivates the surface defect states on InN and might be an effective method to prepare InN films for electronic applications. A model for the improved electron transport properties is proposed taking into account the decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…The downward band bending was varied in reasonable limits bearing in mind the value -0.9 eV with respect to the Fermi level in bulk InN. 13 These results are depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The downward band bending was varied in reasonable limits bearing in mind the value -0.9 eV with respect to the Fermi level in bulk InN. 13 These results are depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 98%
“…[13] Among the mechanisms determining the apparent concentration of carriers, the accumulation of electrons at the InN surface was found to be manipulated by the formation of a thin surface oxide layer. The reduction of the net carrier density of the InN epilayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently observed that In 2 O 3 layers grown on InN can enhance the carrier mobility. 24 Since the InN NWs reported in this study are covered with a thin shell of In 2 O 3 , this could also be a possible reason for the increased mobility compared to earlier studies. However, it should be noted that the mobility of the carriers in the InN NWs is still much lower than the carrier mobility of 1000 to 3000 cm 2 /V s measured in thin films.…”
Section: Electrical Transport Propertiesmentioning
confidence: 88%
“…Previous studies have shown, that the high electron concentration consists of different contributions [4,5]: (i) high electron sheet concentration at the surface and interface, which origin is still under investigation, (ii) a homogeneous background volume concentration and (iii) an inhomogeneous electron concentration over the InN film due to dislocations inside the film [6].…”
mentioning
confidence: 99%